Pulsed Field Gel Electrophoresis (PFGE): a DNA finger printing technique to study the genetic diversity of blood disease bacterium of banana - HADIWIYONO HADIWIYONO; JAKA WIDADA; SITI SUBANDIYAH; MARK FEGAN (Society for Indonesian Biodiversity, 2011)
Hadiwiyono, Widada J, Subandiyah S, Fegan F (2011). Pulsed Field Gel Electrophoresis (PFGE): a DNA finger printing technique to study the genetic diversity of blood disease bacterium of banana. iodiversitas 12: 12-16. Blood disease bacterium (BDB) is the most important pathogen of bananas in Indonesia. In some field, the disease incidence reaches over 80%. Epidemiologically, the disease is similar to Moko disease in South America and Bugtok disease in the Philippines caused by Ralstonia solanacearum race 2. However, BDB is different in phenotype and genotype from the two diseases. Previously BDB was limited in South Sulawesi since 1920s – 1980s and recently was reported in 27 of 30 provinces in Indonesia. Pulsed-Field Gel Electrophoresis (PEGE) is a genomic DNA fingerprinting method, which employs rare cutting restriction endonucleases to digest genome prior to electrophoresis using specialized condition to separate of large DNA fragments. The results showed that PFGE analysis was a discriminative tool to study the genetic diversity of BDB. Based on the PFGE analysis, BDB isolates obtained from different localities in Yogyakarta and Central Java were quit diverse.